Use of the Swiveling Technique for Endoscopic Removal of a Colloid Cyst of the Third Ventricle: A Technical Note - Dorsch, Alexander B.; Leonardo, Jody (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Colloid cysts are considered benign brain tumors and usually occur in the anterior third ventricle. The clinical presentation may be nonspecific and heterogeneous including headaches, visual changes, nausea, and vomiting. The symptomatology is frequently associated with the development of hydrocephalus. Neuroendoscopic removal is increasingly replacing open microsurgical approaches as the standard of care for the treatment of symptomatic colloid cysts of the third ventricle. We describe the case of a 42-year-old man who was found to have a colloid cyst of the third ventricle while undergoing evaluation for a dural arteriovenous fistula. We highlight the rotational, or “swiveling,” method for extraction of the colloid cyst.
Keywords: colloid cyst; neuroendoscopy; minimally invasive neurosurgery